Factors Related to Implementation Covid-19 Vaccination in the Elderly - Hastuti, Puji; Putri, Dian Utama Pratiwi; Budiati, Endang Pratiwi (Global Health Science Group, 2022)
Covid-19 vaccination is the government's way to fight and deal with COVID-19 in Indonesia. There are still many groups of people who refuse the Covid-19 vaccine for various reasons. The purpose of this study was to determine the factors related to the implementation of the covid-19 vaccination in the elderly in the working area of ​​the Satellite Inpatient Health Center in Bandar Lampung City in 2021. Design This research is analytic with cross sectional approach. The number of samples in this study were 81 respondents, the sampling technique was Cluster Random Sampling, bivariate analysis using Chi Square. The results of the univariate study showed that respondents with good knowledge were 31 (38.27%), respondents with positive attitudes 47 (58.03%), respondents with positive family support 55 (67.91%), respondents with positive staff support 46 (56 ,80%). The results of the bivariate test showed that there was a significant relationship between knowledge, attitude, family support, and support from health workers with the implementation of the covid-19 vaccination in the Work Area of ​​the Bandar Lampung Satellite Inpatient Health Center in 2021.